Corruption and Foreign Direct Investment (FDI) in ASEAN-5 : A Panel Evidence - Bakri, Bin Abdul Karim; Zulkefly, Bin Abdul Karim; Mohamad Naufal, Bin Nasharuddin (Economics and Finance in Indonesia (EFI), 2019)
This paper examines the effects of corruption on the inflow of FDI in ASEAN-5 countries by controlling two macroeconomic variables namely Gross Domestic Product (GDP) and inflation. Using a static panel data estimation, the results show the significant relationship between corruption and Gross Domestic Product (GDP) on the inflow of FDI in ASEAN-5. This results indicate that less corrupted countries and larger market size would attract more FDI inflows. The policy implications from this study suggests that ASEAN-5 governments need to have concerted and continues efforts in improving the integrity and credibility of their administration and transactions. In addition, maintaining their sustainable of economic growth is also crucial as a full factor in attracting more FDI inflows in future.